Mezi filosofií a medicínou. Ke Kantovu překonání karteziánského dualismu mysli a těla - Pech, Robin (Filosoﬁcký časopis)
The aim of the study is to show that one of the essential motifs of Kant’s critical philosophy is the issue of human health. Its starting point is therefore Kant’s reflections in the Metaphysics of Morals (1797) and the Conflict of the Faculties (1798), where Kant presented his concept of so-called “universal medicine,” which focuses on the problem of a healthy regimen. Since its basic assumption is that the body and mind of a person, however different they might be, are mutually connected so that the diseases of the body can be cured by way of the mind, it is the author’s interpretation that this concept is a peculiar attempt to overcome the substantive dualism of mind and body seen in Descartes’ Meditations on First Philosophy (1641). At the same time, however, Kant follows on from what Descartes himself attempted.